Fallout and Fertility: Chernobyl's Legacy and the Role of Compliance with Public Protection Measures - Matilde Giaccherini; Joanna Kopinska (CESifo GmbH, 2024)
This paper examines the impact of early-life radiation exposure on adult fertility using a dynamic difference-in-differences approach. Analyzing 18 cohorts of women born between 1976 and 1993 in Italian municipalities, we utilize a radiation exposure indicator and administrative datasets on hospitalizations (2004-2016) and birth certificates (2002-2019). Findings show increased rates of thyroid complications and cancer among women exposed in utero or up to five years old, along with higher incidences of spontaneous abortions and stillbirths. Finally, municipalities with high agricultural employment experienced more severe fallout effects, while political beliefs did not significantly influence adherence to protective measures.
Keywords: 330; fertility; radiation exposure; public health; health behaviors